2003
DOI: 10.1016/s1074-7613(03)00206-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by C5a of Neutrophil Activation during Sepsis

Abstract: In sepsis, there is evidence that excessive C5a generation leads to compromised innate immune functions, being associated with poor outcome. We now report that in vitro exposure of neutrophils to C5a causes increased levels of IkappaBalpha, decreased NF-kappaB-dependent gene transcription of TNFalpha, and decreased lipopolysaccharide (LPS)-induced TNFalpha production. Similar findings were obtained with neutrophils from cecal ligation/puncture (CLP)-induced septic rats. Such changes were reversed by antibody-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 28 publications
6
82
1
1
Order By: Relevance
“…The consequences of combined signaling by C5a and UDP in macrophages may be particularly important in areas of inflammation, where C5a is produced, and where UDP may be released from dying cells (59). C5a in particular plays a central role in inflammation, and consequences of Ca 2ϩ signaling would be augmented by UDP, whereas consequences of PI3K activation would be inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of combined signaling by C5a and UDP in macrophages may be particularly important in areas of inflammation, where C5a is produced, and where UDP may be released from dying cells (59). C5a in particular plays a central role in inflammation, and consequences of Ca 2ϩ signaling would be augmented by UDP, whereas consequences of PI3K activation would be inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…There are no published data that definitively support a direct linkage or intersection between the C5aR and TLR4 pathways (16,42,43). However, there are several reports that indicate the ability of C5a to alter the outcomes of LPS-induced activation of phagocytic cells (16,26,44,45). Recently, it has been reported that the induction of the IL-12 family of cytokines in activated macrophages was suppressed in the copresence of C5a, potentially setting the stage for the immunosuppressive effects seen in sepsis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage tolerance, a state of decreased responsiveness of inflammatory gene expression, has been shown to be associated with increased expression of the IB and IB genes (30). Recently, increased IB␣ expression has been linked to C5a-induced inhibition of lipopolysaccharide-dependent tumor necrosis factor ␣ production in neutrophils (31). Other studies have demonstrated decreased NF-B activation in response to increased levels of IB␣ induced by transforming growth factor ␤1 in human salivary gland cells (32).…”
Section: Discussionmentioning
confidence: 99%